The prevalence of burnout and depression in medical doctors working in the Cape Town Metropolitan Municipality community healthcare clinics and district hospitals of the Provincial Government of the Western Cape: A cross-sectional study - L. Rossouw; S. Seedat; R.A. Emsley; S. Suliman; D. Hagemeister (South African Family Practice)
Aim: This study investigated burnout and depression in medical doctors in the context of work-related conditions and the role of resilience as a modifiable factor.